2018
DOI: 10.1136/bjophthalmol-2018-312125
|View full text |Cite
|
Sign up to set email alerts
|

Vision and visual potential for perifoveal retinoblastoma after optical coherence tomographic-guided sequential laser photocoagulation

Abstract: Anatomical visual potential and functional vision were better in juxtafoveal than foveolar retinoblastoma treated with foveal-sparing laser photocoagulation guided by OCT. The role of amblyopia therapy requires a prospective study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 34 publications
1
10
0
Order By: Relevance
“…The data were obtained retrospectively. There authors did not have access to optical coherence tomography images to assess foveal anatomy before and after treatment, something that has been shown to be affected by laser [14]. The patients and eyes in this study were treated by four different retinoblastoma specialists at two different centers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The data were obtained retrospectively. There authors did not have access to optical coherence tomography images to assess foveal anatomy before and after treatment, something that has been shown to be affected by laser [14]. The patients and eyes in this study were treated by four different retinoblastoma specialists at two different centers.…”
Section: Discussionmentioning
confidence: 99%
“…The addition of laser causes a progressive scar that may affect vision [9], may increase the rate of vitreous recurrence [10], and has been shown to result in orbital recurrence [11]. Conversely, combining thermal laser with systemic chemotherapy increases the rate of tumor control compared to chemotherapy alone [12,13] and recent research suggests that the foveal anatomy can be preserved with foveal-sparing laser even with parafoveal tumors [14]. There have been no clinical trials testing the effectiveness and long term side effect profile of adjuvant laser for the treatment of retinoblastoma [15].…”
Section: Introductionmentioning
confidence: 99%
“…Historically, eyes with RB had a guarded prognosis. Recent studies have demonstrated improved visual outcomes 1723. A study that evaluated visual outcomes in 12 children with macular RB found that 80% of eyes with macular involvement had improvement of visual acuity following occlusion therapy 21.…”
Section: Discussionmentioning
confidence: 99%
“…6,9 11 Even though the current treatment options achieve excellent local tumor control, the final visual outcomes depend on the size and location of the tumor as well as the administration of adjuvant laser TTT in the macular area. 9,10,12,13…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies reported good tumor control using primary IVC without the use of laser treatment, 5 while others advocated the use of IVC for chemoreduction followed by adjuvant laser application to the nonleading edge of the tumor. 6,[9][10][11] Even though the current treatment options achieve excellent local tumor control, the final visual outcomes depend on the size and location of the tumor as well as the administration of adjuvant laser TTT in the macular area. 9,10,12,13 In patients treated with laser TTT for macular RB, the visual acuity (VA) after treatment is reported to be 20/200 or better in 20% to 63% of patients.…”
Section: Introductionmentioning
confidence: 99%